Endometrioma in post cesarean surgical wound. Presentation of a female patient - Ángel F. Gálvez Puyuelo; Rafael Abelardo Cardet Fleites; María Elena Benavides Casal (Acta Médica del Centro, 2016)
The endometrioma of abdominal wall, especially in the scar of surgical wound post caesarean, constitutes one of the varieties of presentation of the endometriosis; though it presents low incident, it is common as a cause of tumors of abdominal wall and the treatment is surgical. A female patient case is presented with a post surgical neoplasms to four years of a caesarean that presented symptomatic variations and increase of volume in relation with the menstruation. She was submitted to surgical managing by finding of endometrioma of wall abdominal and managed with total split by wide edges by good post surgical response and without relapse.